Investigation of Teachers\' Lived Experiences of Student\'s Bullying Behavior: A Phenomenological Approach - Narges Pourtaleb; Eskandar Fathi Azar; Yousef Adib (Kerman University of Medical Sciences, 2019)
Introduction: Bullying is a complicated behavioral problem that is mostly occurs at schools. There are many quantitative studies on this issue but few qualitative studies have investigated this problem. Therefore, this study was performed to investigate teachers' lived experiences of student's bullying behavior. Method: This is a qualitative study with a phenomenological approach. In this study, 20 high school teachers were selected using Purposive sampling. Data were collected using semi-structured interviews and analyzed using Smith method. Results: After data analysis, 5 main themes and 23 sub-themes were extracted. It was revealed that in the definition of bullying, examples, features, and causes, there is a consistency between the teachers' lived experiences and background, but in feedbacks, different results were obtained. Teachers, based on their personal preferences, use different methods such as punishment, individual negotiation, referral to the manager's office, ignoring the undesirable behaviors and strengthening their conflicting behaviors, finding the causes, showing affection and creating friendship, inviting parents, referral to psychologists to take advice, and taking the rules of the school, scoring, and discipline seriously. Conclusion: The results of this study will pave the way for further research on the interventions related to bullying.